Big in the Big Ten: Highly Cited Works and Their Characteristics. Issue 4 (1st October 2020) - Dotson, Daniel S.
ABSTRACT: For this study, the 100 most highly cited items from Scopus were examined for each Big Ten Academic Alliance school (plus University of Chicago) to determine format use, subjects covered, citation counts, publisher trends, and other details. In all, 1, 223 unique items were examined. Journals and commercial publishers dominated, but were not exclusive. Similarly, expected titles Science and Nature appeared, but did not overwhelmingly dominate the citation counts nor the number of appearances in the results. The publication title list included 479 unique titles, with many journal titles appeared only once. Science titles dominated, with some social sciences (especially psychology) titles showing up in the highly cited list. Total citation counts varied widely across institutions. The schools examined had a good degree of inter-institution collaboration.